Примарна дисменореjа - епидемиолошки и доплер ултразвучни карактеристики кај студентска популација во Република Северна Македонија - Иванова Панова, Даниела (Медицински факултет, УКИМ, Скопје, 2020)
Introduction: Primary dysmenorrhea, painful monthly bleeding without any sort of visible organ substrate represents a very common state in the adolescent female population. The etiology is explained through the synergy between the hypercontractility of the myometrium and the excessive production of prostaglandins. Recently, immune factors, as well as the production of some inflammatory mediators, have also been mentioned among the aforementioned factors. Risk factors have also been identified, factors which contribute to the appearance/creation of variety in the symptomatology for whose grading there is the existence of different scales and systems. Furthermore, the existence of variety in the uterine blood flow being in correlation with the menstrual phase of the uterus is concluded, however, the aforementioned differences are significantly heightened in patients with dysmenorrhea. Aims: The purposes of the study were the determination of the prevalence of primary dysmenorrhea within our population, the risk factors, the grading of the symptomatology, the observation of the handling of the situation, the measurement of the uterine flows during the cycle in girls with and without dysmenorrhea in order to conclude the existence of regularity. Materials and Methodology: This doctoral dissertation consists of two parts. The first part is a cross sectional study with the aid of a questionnaire received from 847 female students, in their first or second year of university, gathered from three state universities in the Republic of North Macedonia. The questionnaire consists of blocks of questions, consisting with questions surrounding demographical information, information concerning nutrition and diet, general habits, as well as information of personal, familial and gynecological anamnesis. Afterwards, the participants with dysmenorrhea receive the opportunity to rate the strength of the symptomatology with the aid of two tools: a Visual-Analogue Scale and a system with individual symptoms. At the end, there is a block of questions which give insight into the impact of the situation on the participant’s the everyday activities, as well as the way the participant deals with the condition. The second part of the dissertation consists of a longitudinal case-control study in which 96 girls (out of which 70 are with primary dysmenorrhea and 26 are without the condition, serving as the control group) were examined through ultrasound, and had the blood flow within the uterine blood vessels measured. The same participants were examined during the luteal phase and during first to second day of the menstrual flow with a transabdominal probe. Results: The prevalence of dysmenorrhea in our population is 72,4%. From the aforementioned risk factors, the consumption of cigarettes with p value < 0,003 displayed itself significantly more common with the students with dysmenorrhea. Almost 85% of the participants with dysmenorrhea possessed positive familial anamnesis (p<0,001) Irregular cycles (p<0,002) as well as abundant monthly flows (p<0,0038) appeared to be significantly more common with the participants with dysmenorrhea. Through the quantification of the pain with the Visual-Analogiue Scale, half of the participants rated the condition with a medium score 6,35 ± 2,2, one half of the participants possessed mild dysmenorrhea and rated the pain with a score between 4 and 7 on the same scale. The correlation between the Visual-Analogue Scale and the system of individual symptoms displayed distinct significance. Through the usage of the univariate logistic regression analysis for the testing of predictive factors, the participants with heavy flows are twice more likely to possess primary dysmenorrhea (ОR=2,1, 95% CI 1,078-4,221). The multivariate logistic regression analysis displayed that positive familial anamnesis for dysmenorrhea enhanced the possibility for the presence of primary dysmenorrhea around 2,7 times (ОR=2,68, 95% CI 1,082-1,93). The ultrasound examinations/measurements displayed significantly higher values on the Resistance Index (RI) of the uterine arteries bilaterally during the menstrual phase, however, as well as during the luteal phase in the participants with primary dysmenorrhea in comparison with the control group. The Pulsatility Index (PI) displayed significant difference between the groups only during the period of menstruation. These sorts of findings repeated themselves with the arcuate arteries as well. The correlation between the blood flow and the intensity of the pain measured with the Visual-Analogue Scale displayed the existence of a direct/positive correlation according to the Spearman coefficient. During the menstrual phase, the intensity of the pain is significantly correlated with the Resistance Index and the Pulsatility Index of both the uterine arteries (p=0,0068, p=0,00047) Conclusion: The primary dysmenorrhea is a common condition within our population. The condition needs further addressing from both professionals as well as the system itself. The education of the youth, young women and girls especially, as well as the access to professional care is imperative for timely diagnoses of the condition, proper treatment as well as prevention from future reproductive problems.
Primary dysmenorrhea-epidemiological and Doppler ultrasound characteristics among student population in Republic of North Macedonia
Докторска дисертација одбранета во 2020 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Бети Зафирова Ивановска.
Keywords: Primary dysmenorrhea, risk factors, Resistance Index, Pulsatility Index.